Characterization and applications of nanobodies against Pseudomonas aeruginosa Exotoxin A selected from single alpaca B cells. Issue 1 (1st January 2020) - Lin, Jingtao; Gu, Yi; Xu, Yanru; Yu, Jianli; Tang, Jinsong; Wu, Lili; Zhou, Zhengwei; Chen, Cailing; Liu, Minjuan; Chun, Xuan; Liu, Hongling; Nian, Rui; et al.
Abstract: We have established a highly efficient 96-well format based strategy to characterize nanobody (Nb) from an expressed alpaca Nb repertoire by combining heavy-chain antibody variable region gene cloning with Nb expression and reactivity profiling at the single cell level. Individual alpaca B lymphocytes were isolated based on B cell surface marker and membrane type antigen specific antibodies expression by fluorescence activated cell sorting (FACS). Single cell reverse transcription and polymerase chain reaction (PCR) amplification of CH1 and CH2 domain enable the identification and exclusion of B cell clones that express regular antibodies. The corresponding heavy-chain antibody variable region gene transcripts, which are CH1-CH2 domain negative, are then amplified from single B cell clones by nested PCR. Then Nbs were expressed in Escherichia coli cells and four Nbs showed high affinity against Pseudomonas aeruginosa Exotoxin A (PEA). Moreover, two PEA Nbs that recognize unique epitopes on PEA have been successfully applied to protect human cells from PEA induced apoptosis. In summary, our FACS and single cell reverse transcription polymerase chain reaction (RT-PCR) based strategy for identifying recombinant Nbs from single alpaca B cells allows highly efficient and unbiased characterization of the expressed Nb repertoires by sequence analysis, expression and parallel antibody reactivity testing.